Penerapan PSAK 109 Pelaporan Keuangan Akuntansi Zakat dan Infaq/Shadaqah pada LAZISMU: Application of PSAK 109 Financial Reporting Accounting for Zakat and Infaq/Shadaqah at LAZISMU - Hanjani, Andreani; Azizah, Kholifah Nur; Gunawan, Barbara (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to know the implementation of PSAK 109 at LAZISMU and to evaluate the suitability of financial report of LAZISMU with PSAK 109. The research method used in this study is descriptive qualitative. This research was conducted at LAZISMU and the information of the research was obtained from interviews and documentation. The results of the study show that LAZISMU mostly implements PSAK 45 about the financial report of non-profit entities where the profits are not obtained through business but are obtained from social and humanity. In reporting the financial report, LAZISMU only implements the program summary that records each zakat and infaq / sadaqah fund and the percentage given to each asnaf. This is contrast with the implementation of PSAK 109 where the record of financial report consists of the reports of financial position, changes in funds, changes in assets under management, cash flow and notes on financial statements. From the results, it is concluded that the record of financial report at LAZISMU is not fully in accordance with PSAK 109.